2018
DOI: 10.1177/1474515118782100
|View full text |Cite
|
Sign up to set email alerts
|

Improving ambulatory blood pressure monitoring knowledge in nurses and doctors: impact of a training intervention

Abstract: Knowledge of ABPM is deficient but can be easily improved by training that is most effective in primary care and among nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…6 Similar to HBPM, physician/PA/ APRNs in our study lacked knowledge of guideline-recommended ABPM diagnostic BP thresholds (ABPM daytime average ≥135 mmHg systolic or ≥85 mmHg diastolic). Daflo-Pibernat et al, in a study conducted in Spain, 25 diagnosing hypertension and initiating treatment were ≥140 mmHg systolic or ≥90 mmHg diastolic for all adult patients. 26 From 2013 to 2017, the guidelines changed, incorporating a threshold of ≥150 mmHg systolic for adults aged 60 and over.…”
Section: Discussionmentioning
confidence: 97%
“…6 Similar to HBPM, physician/PA/ APRNs in our study lacked knowledge of guideline-recommended ABPM diagnostic BP thresholds (ABPM daytime average ≥135 mmHg systolic or ≥85 mmHg diastolic). Daflo-Pibernat et al, in a study conducted in Spain, 25 diagnosing hypertension and initiating treatment were ≥140 mmHg systolic or ≥90 mmHg diastolic for all adult patients. 26 From 2013 to 2017, the guidelines changed, incorporating a threshold of ≥150 mmHg systolic for adults aged 60 and over.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, when selecting nurses specifically dedicated to the follow-up of these patients and based on the results obtained, it would make sense to consider the case managers and nurses who had the doctorate and in all cases, and this is especially important in PC, the realisation of a specific training in HF, with those practical tools that have proven their effectiveness (28).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, we must not forget aspects such as an adequate measurement of BP and in this case, we must not forget the use of cuffs of adequate size, so as not to over or underestimate the BP values, until we have ambulatory BP values, whether they are with home monitoring of blood pressure (HBPM) or ambulatory blood pressure monitoring (ABPM) validated (Oliveras Puig et al, 2015). In this second case, the ABPM, the necessary professional competence will increase from different training activities that have demonstrated their effectiveness (Dalfó-Pibernat et al, 2018). Finally, there is also comment on the recent study in which it was shown that there is no inferiority in the titration of HF drugs when HF nurses were compared with cardiologists.…”
Section: Nursing Reflections On the Management Of Hypertension And Hementioning
confidence: 99%